TINJAUAN ALTERNATIF PENYELESAIAN SENGKETA MELALUI MEDIASI DARI PERSPEKTIF UNDANG-UNDANG NOMOR 30 TAHUN 1999 - Wira ChandraHadiningrat, A. A. N.; Rai Asmara Putra, Dewa Nyoman; A. Martana, Nyoman (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2014)
This undergraduate thesis entitled: Overview of Alternative Dispute Settlement Through Mediation From the Perspective of Law Number 30 of 1999. The study is a normative writing that addresses two issues, Firstly on What are the Alternative Dispute Settlements accordin to the Law Number 30 of 1999. Secondly, what is the pocess of Mediation as an Alternative Dispute Settlement in Indonesia.The business world is very appreciative of all the possible settlement of disputes and it needs help to use it effectively. Dispute settlements can provide a real difference to productivity and business operations and profits. Only a small number of lawyers and other fields that have sufficient knowledge about the dispute settlements so that they are able to educate their clientsand suggested that they should take advantage of the dispute settlements through Alternative Dispute Settlement. It seems that in society, only few are aware of the advantages of settling disputes through this way. It takes a two-pronged approach to educate the legal profession and the business community regarding the settlement o disputes. According to Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Settlement, specifically to Alternative Dispute Settlement, they are 4 ways of dispute settlements, namely Consultation, Negotiation, Mediation, and Conciliation.Guidelines need to be developed for businesses in order to take advantage of the Alternative Dispute Settlement effectively. The business world needs to be trained about the strengths and weaknesses of each of the dispute settlement process and how to utilize these processes effectively. The pattern of individual dispute settlement process begins with the formation of a reliable negotiating team of which parties have a specific strategy in order to reach the goal and it is very necessary and understandable that both the legal practitioners and the entrepreneurs use the services of a mediator in the settlement of business disputes. The businessmen are expected to be smart in chossing an effective and efficient dispute settlement patterns.
Keywords: Alternative Dispute Settlement, Mediation, the Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Settlement